Effects of Mn2+ and Mg2+ on assimilation of NO3- and NH4+ by soil microorganisms. - McCarty, G W (1993)
Although it has been demonstrated that Mn2+ and Mg2+ can influence the activity of glutamine synthetase in various organisms, there is little information concerning the effects of these cations on the activity of this enzyme in soil microorganisms or on ability of these microorganisms to assimilate NO3- and NH4+. We studied the effects of different concentrations of Mn2+ and Mg2+ on assimilatory NO3- reduction and NH4+ assimilation in cultures of two microorganisms commonly found in soil [Pseudomonas fluorescens (ATCC 13525) and Azotobacter chroococcum (ATCC 9043)] and in an enrichment culture of soil microorganisms. We found that Mn2+ strongly inhibited NH4+ assimilation by soil microorganisms and blocked the inhibitory effect of NH4+ on assimilatory NO3- reductase (ANR) activity, thereby uncoupling ANR activity from nitrogen assimilation and causing the NH4+ formed by ANR activity to be released to the environment. Mg2+ counteracted the effect of Mn2+ on microbial metabolism of nitrogen, which suggests that the overall effect of these cations on nitrogen assimilation by soil microorganisms will depend on the ratio of their concentrations in soil.